Mechanical Analysis of Mining Stress Transfer on Isolated Island Face in Extra-Thick Fully Mechanized Top-Coal Caving Mining - Min Tu; Qingwei Bu; Baojie Fu; Yu Wang (Geofluids)
The mining spatial structure of isolated island face in extra-thick fully mechanized top-coal caving mining is unique, which leads to a complex mining stress distribution and serious safety hazards. In this study, combined with a specific engineering example, the mining stress distribution characteristics of isolated island face are expounded, and a bearing structural mechanical model of the continuous beam of overlying strata is established using elastic–plastic mechanics theory. The mechanical equations of the mining stress distribution and failure depth of coal–rock mass are then obtained. Comparison of theoretical calculation results with numerical simulation and field measurement results shows basically consistent stress distribution characteristics. The derived mechanical equations can provide an estimation method for the analysis of mining dynamics on isolated island face in extra-thick fully mechanized top-coal caving mining. The following conclusions are acquired. The coal–rock mass should bear not only the lateral mining superposition influence but also the advance mining influence in front of the coal wall, so the isolated island face is in the complex environment of multiple mining stress superposition. In the mining process, the maximum advance mining stress concentration factor is 4.0–6.0 and is located at the upper and lower ends of the isolated island face. The lateral mining failure depth of the coal wall of the isolated island face increases by 2.0–5.0 m under the influence of advance mining. Therefore, compared with the nonisolated island face, the mining pressure appearance is intense. The mining influence in the range of 20–30 m of the upper and lower ends is intense, and the mining stress in this area is characterized by “cone distribution.” This zone is an important hidden danger area with coal–rock mass mining instability on isolated island face, which requires special attention to avoid mining disasters. According to the analysis of the influencing mining factors and laws of isolated island face, it is concluded that the longer the isolated island face size is, the closer the goaf size on both sides of the isolated island face is, the smaller the coal seam buried depth is, the better the mechanical conditions of coal and rock medium are, and the smaller the mining height of coal seam is, the more favorable the safe mining of isolated island face is.